Social work and social development theories and skills for developmental social work - Midgley, James; Conley, Amy. (New York ; Oxford : Oxford University Press, 2010)
This book shows the relevance of developmental social work to the US and other Western nations, contending also that its practice is not confined to community organisation or other macro-practice interventions, and that developmental ideas can be implemented in mainstream fields such as child welfare, mental health, aging, etc.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Social service -- Case studies